High resolution CT and histological findings in idiopathic pleuroparenchymal fibroelastosis: Features and differential diagnosis - Piciucchi, Sara (BioMed Central, 2011)
Idiopathic pleuroparenchymal fibroelastosis (IPPFE) is a recently described clinical-pathologic entity characterized by pleural and subpleural parenchymal fibrosis, mainly in the upper lobes. As this disease is extremely rare (only 7 cases have been described in the literature to date) poorly defined cases of IPPFE can go unrecognized. The clinical course of disease is progressive and prognosis is poor, with no therapeutic options other than lung transplantation currently available, yet. The aim of this report is to describe two further cases of this rare disease, reviewing CT, clinical and histological features.